Validation of the Bipolar Recovery Questionnaire for the Portuguese Population: Recovery and Predictors in People with Bipolar Disorder - Julieta Azevedo; Diogo Carreiras; Raquel Guiomar; Maria João Martins; António Macedo; Paula Castilho (Acta Médica Portuguesa, 2024)
Introduction: The paradigm in mental health care is progressively moving towards a recovery-focused perspective. Thus, there is a need for validated instruments to measure recovery in bipolar disorder (BD). The Bipolar Recovery Questionnaire (BRQ) is the most used instrument to assess it. The aim of this study was to translate and perform a cross-cultural adaptation of the BRQ to European Portuguese (PT-PT) and to explore further associations of recovery with sociodemographic and emotional regulation, as well as recovery predictors to inform future research and clinical practice. Methods: The BRQ was forward-translated and back-translated until a consensus version was found, and a test-retest design was used to assess temporal stability. Participants were recruited in public hospitals and organizations supporting people with BD, either referred by their psychiatrists or psychologists or through self-referral. Eighty-eight individuals diagnosed with BD were recruited to complete a battery of Portuguese-validated self-report questionnaires to assess recovery (BRQ), clinical mood symptoms (Hospital Anxiety and Depression Scale), affect (Positive and Negative Affect Scale), well-being (brief Quality of Life for Bipolar Disorder; Satisfaction with Life Scale) and emotion regulation (Difficulties in Emotion Regulation Scale). Results: The BRQ showed excellent internal consistency with a Cronbach alpha of 0.92, and test-retest exhibited good reliability (r = 0.88). Construct validity was confirmed through/by positive and moderate correlations with quality of life (QoL; r = 0.58) and positive affect (r = 0.52), and negative moderate correlations with depression (r = -0.64), and negative affect (r = -0.55). Both satisfaction with life (β = 0.38, p = 0.010) and recovery (β = 0.34, p = 0.022) impacted quality of life, supporting the BRQ’s incremental validity. Depressive symptoms and emotion dysregulation accounted for 51% of its variance. Conclusion: The BRQ is a valid and reliable instrument to measure recovery in people with BD in the Portuguese population and is suitable for both clinical and research contexts.